2009
DOI: 10.3174/ajnr.a1434
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Study on Ultra-High-Field MR Imaging in Patients with Multiple Sclerosis: Comparison of 1.5T and 7T

Abstract: BACKGROUND AND PURPOSE:Higher magnetic field strengths and continuous improvement of highresolution imaging in multiple sclerosis (MS) are expected to provide unique in-vivo and non-invasive insights in pathogenesis and clinical monitoring. The purpose of this study was to investigate the potential of high-resolution imaging of MS lesions in vivo comparing 7T with conventional 1.5T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
128
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 18 publications
1
128
1
4
Order By: Relevance
“…This perivenous configuration of MS lesions has been recently demonstrated using T2*‐weighted ultrahigh‐field 7T MRI,13, 15 and in studies that have included non‐MS populations, the quantification of CVs has predicted a diagnosis of MS 12, 14, 17, 27, 28, 29. Several studies reported detection of CVs in lesions of MS patients more frequently than other populations, including patients with Susac syndrome29 and neuromyelitis optica spectrum disorder,17 and controls with high risk for vascular disease 28.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This perivenous configuration of MS lesions has been recently demonstrated using T2*‐weighted ultrahigh‐field 7T MRI,13, 15 and in studies that have included non‐MS populations, the quantification of CVs has predicted a diagnosis of MS 12, 14, 17, 27, 28, 29. Several studies reported detection of CVs in lesions of MS patients more frequently than other populations, including patients with Susac syndrome29 and neuromyelitis optica spectrum disorder,17 and controls with high risk for vascular disease 28.…”
Section: Discussionmentioning
confidence: 81%
“…One such method may be detection of the “central vessel sign” (CVS) 10. It has been known from histopathological studies at autopsy that most MS lesions are centered around veins,11 and only recently have a variety of imaging techniques using susceptibility‐weighted imaging on ultrahigh‐field 7‐tesla (T) research magnets demonstrated this relationship in vivo 12, 13, 14, 15, 16, 17. A small number of studies have also evaluated the ability of 3T scanners, which are used routinely in clinical practice, to detect a “central vessel” (CV) in MS lesions 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The introduction of ultra-high-field 7T systems has led to improved detection and classification of cortical lesions in patients with MS, mainly by using experimental T2*-weighted gradient-echo sequences. [17][18][19][20] The depiction of cortical GM by using the standard imaging protocol for MS, 21 including T1WI, T2WI and FLAIR sequences, has not yet been investigated at 7T and neither has the use of DIR at 7T. This is mainly due to the challenging application of 3D FLAIR and DIR sequences on a 7T system, because of, among others, specific absorption rate restrictions.…”
mentioning
confidence: 99%
“…MR imaging in detecting lesions with cortical involvement 11 and up to 69% more sensitive than 3T double inversion recovery (DIR) imaging in detecting subpial lesions. 10 Few groups have had the opportunity to study GM lesions that were visualized with 7T T2*WI in terms of histopathology.…”
mentioning
confidence: 99%